2013
DOI: 10.1590/s1516-89132013000500015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of integral and decaffeinated coffee brews on metabolic parameters of rats fed with hiperlipidemic diets

Abstract: The objective of this study was to evaluate the influence of integral and decaffeinated coffee brews (Coffea arabica L and C. canephora

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…However, it may be due to the variations in the mode of coffee administration. Lipid lowering effects of coffee found in the present study could be related to caffeine, (methylxanthine) which stimulates lipolysis by increasing cellular levels of cAMP through antagonism adenosine receptors (A1) and inhibition of phosphodiesterase activity [25,27].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, it may be due to the variations in the mode of coffee administration. Lipid lowering effects of coffee found in the present study could be related to caffeine, (methylxanthine) which stimulates lipolysis by increasing cellular levels of cAMP through antagonism adenosine receptors (A1) and inhibition of phosphodiesterase activity [25,27].…”
Section: Discussionmentioning
confidence: 62%
“…Evaluation of fasting serum lipid profiles showed that treating rats with 284 mg/kg BW/day of coffee had significantly lowered fasting serum levels of TG and LDL-C when compared to fructose control group (p = 0.031; 0.046) respectively. Consistent with these findings, Gomes et al reported that feeding of 7.2 mL/kg of body weight for 41 days significantly lowered lipid percentage in hyperlipidemic diet feeding rats [25]. In addition, Li et al reported CGA significantly lowered the levels of fasting serum TG, FFA, TC, and LDL-C in golden hamsters [18].…”
Section: Discussionmentioning
confidence: 73%
“…It was like pectin polysaccharide. 11 Pectin is one of some species which water-soluble food and easy to fermented by intestine microflora. Because the compound of pectin inside is a good fiber source.…”
Section: Resultsmentioning
confidence: 99%
“…About 120 adipocytes per region evaluated for each animal were randomly analyzed by ImageJ software. The following parameters were evaluated: (i) diameter, measured from the greatest distance between the edges of the cells; (ii) area, calculated from its delimitation; and (iii) density, using the square of the known area superimposed on certain fields of the captured images 22 …”
Section: Methodsmentioning
confidence: 99%